Compact Double Shorted Loop Sub-6-GHz Dual-Band MIMO Quad-Antenna System - Shu-Chuan Chen (IEEE Access, 2021)
This paper presents the design of a compact double-loop sub-6-GHz dual-band MIMO quad-antenna system for 5G laptops. To meet the market demand for laptops with a high screen-to-body ratio, the sub-6-GHz dual-band MIMO quad-antenna system is realized to have a low-profile height of only 3 mm. To make the MIMO quad-antenna system suitable for laptops with a narrow bezel, the four antenna elements are printed on the same FR4 substrate, which is mounted on the upper edge of and coplanar with the display ground plane of a laptop. The four antenna elements have the same double shorted loop structure and the same size of $15× $ 3 mm2. In the loop structure, a meandered path is embedded in one of the two shorted-end sections, and a series chip capacitor is embedded in the other. The low-frequency resonance mode can be adjusted by varying the meandered path, and the high-frequency resonance mode can be tuned using the meandered path and the series chip capacitor. The four antenna elements are aligned in the same direction with an end-to-end gap of 5 mm so that satisfactory isolation can be achieved without any additional isolation elements. The MIMO quad-antenna system, although measuring only $75× $ 3 mm2 with the three gaps included, can cover 3400–3800 and 4800–5000 MHz for 5G dual-band operations. The measured isolations between the four antenna elements are larger than 10 dB, the envelope correlation coefficient (ECC) values calculated from the measured radiation patterns are all below 0.27, and the measured radiation efficiencies of all four antenna elements are over 42%.